Estudo comparativo entre curvas-chave empíricas e sintéticas para gerenciamento de riscos de inundações urbanas: o caso de São Carlos, SP - Souza, Marina Fagundes e (Universidade Federal de São Carlos, 2026)
Brazil suffers from periodic floods, flash floods, inundations, and urban waterlogging. Some of the causes include: the notion that nature should "adapt" to human needs and desires; urbanization and, consequently, the rapid, uncontrolled, and indiscriminate sealing of urban soils; and a historical preference for "gray engineering" solutions. Thus, it is increasingly necessary to efficiently predict the occurrence of floods. A major difficulty in making such predictions, however, is the lack of hydrological monitoring data, especially flow data. Synthetic rating curve methods have emerged as an alternative. This research aims to generate theoretical rating curves for water bodies in São Carlos using PCSWMM software, and to compare theoretical and empirical curves. The study involved a literature review, data collection and survey, hydrodynamic modeling in PCSWMM, and a comparison between empirical and synthetic rating curves. The development of a hydrodynamic model and the generation of synthetic rating curves open up new possibilities for understanding urban flood processes. Furthermore, they represent progress toward improving the quality of risk management during extreme events. The model developed in this study resulted in a synthetic rating curve capable of adequately representing the overall dynamics of the events, especially the peaks and peak times—that is, the shape of the hydrograph. However, the curve tends to overestimate low flows and underestimate very high flows. Despite these limitations, it is concluded that the synthetic rating curve obtained is indeed applicable to urban flood risk management.
Comparative study between empirical and synthetic rating curves for urban flood risk management: the case of São Carlos, SP
Keywords: Saneamento básico; Drenagem urbana; Inundações urbanas; Modelos hidrológicos; Curvas-chave; Basic sanitation; Urban drainage; Urban flooding; Hydrological models; Rating curves; ENGENHARIAS::ENGENHARIA CIVIL::ENGENHARIA HIDRAULICA::HIDROLOGIA; 9. Indústria, Inovação e Infraestrutura; 11. Cidades e Comunidades Sustentáveis